Gambaran Biologi Perempuan dalam Kumpulan Puisi Catatan-Catatan dari Bulan Karya Rieke Saraswati - Armalina Armalina; Yenni Hayati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe the biological aspects of women contained in the poetry collection of "Catatan-Catatan dari Bulan" by Rieke Saraswati. This study uses a qualitative approach with a gynocritic approach that produces descriptive data in the form of written words. The author uses this biological aspect in his poetry to convey the mindset of resistance, dissatisfaction, and suppression experienced by women in society regardless of age. Based on the data analysis, 34 data about the biological aspects of women were found in the poetry collection of "Catatan-Catatan dari Bulan" by Rieke Saraswati. The biological aspects found in Rieke Saraswati's poetry collection of "Catatan-Catatan dari Bulan" using a gynocritic approach include four aspects, namely (1) female self-identity, which includes puberty, menstruation, pregnancy, childbirth, and breastfeeding; (2) women's sexual expression, in this aspect the author breaks the tradition in Indonesia which considers women's sexuality to be something that must be strictly controlled; (3) resistance to patriarchy, the author voices protest and opposition in response to things that befell women; and (4) the issue of gender inequality, this aspect is found chiefly in the poetry collection of "Catatan-Catatan dari Bulan", the author voices the injustices that women often experience. The aspect of celebrating women's biology is not found in Rieke Saraswati's poetry collection of "Catatan-Catatan dari Bulan". In this collection of poems, the author reveals the deprivation of women's rights in society.